Ukrainian flora checklist. 13: families Plumbaginaceae and Polygonaceae (Polygonales, Angiosperms) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Materials and methods: Analysis of the herbarium collections, literature data, field observations. Nomenclature: POWO 2025, Euro+Med Plant Base 2025, Hassler 2025. Results: In the flora of Ukraine, the order Polygonales includes two fami-lies, Plumbaginaceae and Polygonaceae. The family Plumbaginaceae is represented by four genera, namely Armeria (A. elongata), Ceratostigma (C. plumbaginoides), Goniolimon (four species) and Limonium (12 species), with two species cultivated (Ceratostigma plumbaginoides – in Crimea, and Limonium sinuatum). Earlier, another species of the genus Armeria, specifically A. pocutica, was reported for Ukraine. However, this species is now considered extinct. Goniolimon desertorum is treated here as a synonym of G. graminifolium, and G. orae-syvashicae is included in G. rubellum. Many nomenclatural changes are accepted in the genus Limonium. In particular, the name Limonium oblongifolium is considered a synonym of L. alutaceum, L. danubiale is synonymous under L. bellidifolium, the names L. latifolium and L. platyphyllum refer to the accepted name L. coriarium, and L. meyeri and L. neoscoparium are included in L. scoparium. The species Psylliostachys spicatus, another species of Plumbaginaceae, was erroneously reported from the territory of Ukraine. The family Polygonaceae is represented in Ukraine by 11 genera and 111 species (both spontaneous and cultivated, together with subspe-cies sometimes considered as separate species, as well as hybridogenic species), which all belong to the subfamily Polygonoideae. In particular, Atraphaxis (two species), Bistorta (two species), Fagopyrum (two species, of which one is cultivated and rarely escaped), Fallopia (five species, of which two are cultivated and escaped), Koenigia (including Aconogon) (four species, of which three are cultivated and escaped), Oxyria (one species), Persicaria (10 taxa, including subspecies that are sometimes considered as separate species), Polygonum (21 species), Reynoutria (five species, cultivated and escaped), Rheum (four species, cultivated) and Rumex (55 taxa, including nothospecies, species of hybridogenic origin and subspecies that are sometimes considered as separate species). Many nomenclatural changes are reported and accepted in the genera Persicaria, Polygonum and Rumex.
Keywords: Biodiversity, annotated list, distribution, species, subspecies, genus, family, systematics, nomenclature, synonyms, herbarium specimens